2015 External Sector Report : Individual Economy Assessments. (Policy Papers; Policy Paper ;, 2015)
The external sector assessments use a wide range of methods, including the External Balance Assessment (EBA) developed by the IMF's Research Department to estimate desired current account balances and real exchange rates (see Annex I of the 2015 External Sector Report, also IMF Working Paper WP/13/272 for a complete description of the EBA methodology). In all cases, the overall assessment is based on the judgment of IMF staff drawing on the inputs provided by these model estimates and other analysis and the estimates are subject to uncertainty. The assessments discuss a broad range of external indicators: the current account, the real effective exchange rate, capital and financial accounts flows and measures, FX intervention and reserves and the foreign asset or liability position. The individual economy assessments are discussed with the respective authorities as a part of bilateral surveillance.